Mechanistic Effect Modeling of Earthworms in the Context of Pesticide Risk Assessment: Synthesis of the FORESEE Workshop. (21st October 2020) - Forbes, Valery E; Agatz, Annika; Ashauer, Roman; Butt, Kevin R; Capowiez, Yvan; Duquesne, Sabine; Ernst, Gregor; Focks, Andreas; Gergs, Andre; Hodson, Mark E; Holmstrup, Martin; Johnston, Alice SA; et al.
ABSTRACT: Earthworms are important ecosystem engineers, and assessment of the risk of plant protection products toward them is part of the European environmental risk assessment (ERA). In the current ERA scheme, exposure and effects are represented simplistically and are not well integrated, resulting in uncertainty when the results are applied to ecosystems. Modeling offers a powerful tool to integrate the effects observed in lower tier laboratory studies with the environmental conditions under which exposure is expected in the field. This paper provides a summary of the (In)Field Organism Risk modEling by coupling Soil Exposure and Effect (FORESEE) Workshop held 28–30 January 2020 in Düsseldorf, Germany. This workshop focused on toxicokinetic–toxicodynamic (TKTD) and population modeling of earthworms in the context of ERA. The goal was to bring together scientists from different stakeholder groups to discuss the current state of soil invertebrate modeling and to explore how earthworm modeling could be applied to risk assessments, in particular how the different model outputs can be used in the tiered ERA approach. In support of these goals, the workshop aimed at addressing the requirements and concerns of the different stakeholder groups to support further model development. The modeling approach included 4 submodules to cover the most relevant processes for earthworm risk assessment: environment, behavior (feeding, vertical movement), TKTD, and population. Four workgroups examined different aspects of the model with relevance for risk assessment, earthworm ecology, uptake routes, and cross‐species extrapolation and model testing. Here, we present the perspectives of each workgroup and highlight how the collaborative effort of participants from multidisciplinary backgrounds helped to establish common ground. In addition, we provide a list of recommendations for how earthworm TKTD modeling could address some of the uncertainties in current risk assessments for plant protection products. Integr Environ Assess Manag 2021;17:352–363. © 2020 SETAC KEY POINTS: Earthworms are important ecosystem engineers that increase soil fertility, provide a wide range of ecosystem services, and are therefore included in risk assessments for pesticides. The (In)Field Organism Risk modEling by coupling Soil Exposure and Effect (FORESEE) Workshop focused on toxicokinetic–toxicodynamic (TKTD) and population modeling of earthworms in the context of environmental risk assessment. Participants addressed various questions relevant to earthworm mechanistic effect modeling related to risk assessment, earthworm ecology, uptake routes, extrapolation and testing against experimental data sets, and ecotoxicological study needs and data gaps. Recommendations for how earthworm TKTD modeling could address some of the uncertainties in current risk assessments for plant protection products are provided.